The role of music therapy in physical rehabilitation: a systematic literature review. - Weller CM; Baker FA (Nordic Journal of Music Therapy, 2011)
Physiotherapists and occupational therapists provide physical rehabilitation to maximize independence of those with compromised function. Qualified music therapists have provided interventions to assist physical rehabilitation for over 20 years, however effectiveness of interventions are often questioned. This systematic literature review explores the effectiveness of music therapy (MT) in physical rehabilitation, the function of music and the role of the music therapist. The following databases were searched: Embase, Cinahl, Allied and Complementary Medicine, Cochrane Review, PsychInfo, Eric, Medline, Dissertation Abstracts and Voices. Research articles were selected if a MT technique was applied towards physical rehabilitation of those experiencing physical impairments. Consistent positive and significant results were found in MT methods in rehabilitation of most gait parameters, and fine and gross motor functioning. The utility of music included increasing motivation, providing an external timekeeper, and providing purposeful and structured rehabilitation interventions. Music therapists were employed to engage patients through music interventions such as instrumental tuition; assess behaviours; adapt interventions according to behaviours; and to provide physical support. These findings suggest that MT enhances physical, psychological, cognitive and emotional functioning within physical rehabilitation. These findings were compared with Staum's (2000) findings in her analysis of music based physical rehabilitation literature from 1950-1999. However, further research is necessary to explore the role of MT interventions in current standard rehabilitation services.